The glue of the world : popular music in film soundtracks : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Media Studies at Massey University - Anderson, Lauren (Massey University, 1999)
Popular music has a strong presence in many contemporary films, frequently replacing, or displacing, the 'classical' soundtrack. The question arises of whether a popular music soundtrack achieves similar functions to traditional, 'classical' film music. Investigating this question is the primary aim of this thesis. An outline of film music theory is followed by an overview of how meaning is produced in popular music. These two areas of discussion are then brought together in the neoformalist analyses of the textual relations between the popular music soundtrack and the narrative, characterisation, and themes of three contemporary films: Sliding Doors (1997, Peter Howitt), Empire Records (1995, Allan Moyle), and Topless Women Talk About Their Lives (1997, Harry Sinclair). The uses and functions of the music in these soundtracks are then compared to the conventions of 'classical' Hollywood film music. This thesis will show that the popular songs in the soundtracks of the three films generally fulfil one or more of six functions which are usually performed by 'classical' Hollywood film music. There are some important differences, however, as the songs frequently draw on features which are specific to popular music. Taken together, the three case studies provide valuable insight into the ways popular music works in contemporary mainstream films.
Keywords: History and criticism; Motion picture music; Popular music